2018
DOI: 10.1007/s10843-018-0235-6
|View full text |Cite
|
Sign up to set email alerts
|

Firm-level entrepreneurship and international performance: A simultaneous examination of orientation and action

Abstract: Relying on the resource-based view and contingency analysis, this study aims to investigate the relationship between firm-level entrepreneurship (FLE) and international performance among Iranian small and medium-sized enterprises (SMEs). The environment is considered as a moderating factor which enables us to discuss the results more precisely. To draw a more holistic picture of entrepreneurship in existing companies, both orientation and action are included in the research model. A survey study of 140 SMEs us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 85 publications
(134 reference statements)
0
16
1
Order By: Relevance
“…To address these gaps, it is argued that strategic renewal mediates the relationship of a firm's EO with both its financial performance and reputation. First, previous studies that examine the link between firm-level entrepreneurship and financial performance have drawn from the resource-based view (Barney, 1991) to conceptualize EO and CE activities as critical, intangible resources (Hosseini et al, 2018;Shirokova et al, 2016). To the extent that these resources are valuable, rare, inimitable and non-substitutable, they can serve as sources of a firm's sustainable competitive advantage and superior financial performance (Wiklund and Shepherd, 2011;Zahra and George, 2002).…”
Section: Government Institutional Supportmentioning
confidence: 99%
“…To address these gaps, it is argued that strategic renewal mediates the relationship of a firm's EO with both its financial performance and reputation. First, previous studies that examine the link between firm-level entrepreneurship and financial performance have drawn from the resource-based view (Barney, 1991) to conceptualize EO and CE activities as critical, intangible resources (Hosseini et al, 2018;Shirokova et al, 2016). To the extent that these resources are valuable, rare, inimitable and non-substitutable, they can serve as sources of a firm's sustainable competitive advantage and superior financial performance (Wiklund and Shepherd, 2011;Zahra and George, 2002).…”
Section: Government Institutional Supportmentioning
confidence: 99%
“…External factors that moderate relationships between the entire constructs of EO/MO and foreign unit performance have been recognized. These include national context (Martens et al 2016;Montiel-Campos 2018;Wales et al, 2013), general environmental uncertainty or dynamism (Dimitratos et al 2004;Sundqvist et al 2012), environmental hostility (Hosseini et al 2018;Zahra and Garvis 2000), competitive intensity (Boso et al 2012;Cadogan et al 2003), and market heterogeneity (Qu and Zhang 2015). Most studies have found positive moderating effects, but the results are inconclusive, given that Sundqvist et al (2012) identified negative moderation effects.…”
Section: Introductionmentioning
confidence: 99%
“…EI may be considered as the key initial phase in the entrepreneurial activity and venture creation development process. The existing literature provides a variety of entrepreneurship definitions -according to GEM, entrepreneurs are defined as "the adult people who are active in an entrepreneurial way in developing a start-up they will partially own or are owing in the present and running an effective infant business (Reijonen and Komppula, 2007;Hosseini, Dadfar, &Brege, 2018). In a broader sense, an entrepreneurial experience comprises of creating a new venture (whether workable or not), a small business that provides employment opportunity (Lee & Wong, 2004).…”
Section: Introductionmentioning
confidence: 99%